Brainstorming workshop and experts consultation on soil salinity monitoring and mapping: perspectives from Global South - Chakraborty, Debashis (International Maize and Wheat Improvement Center, 2023)
This workshop was hosted and organized by CIMMYT (International Maize and Wheat Improvement Center) with support from ICARDA (International Center for Agricultural Research in the Dry Areas), Egypt. The workshop was supported by ICAR (Indian Council of Agricultural Research and ISRO-SAC (Indian Space Research Organization-Space Applications Centre), India. This activity is mapped under two CGIAR initiatives.